Completely Prime and Prime Fuzzy Tðšª-Ideals in TÎ“-Semi rings - Revathi, K; Madhusudhana Rao, D; Sundarayya, P; Satish, T (International Journal of Engineering and Technology, 2018)
C-prime fuzzy TÎ“-ideals and prime fuzzy TÎ“-ideals are studied, then proved some theorem and characterized the C-prime and prime fuzzy TÎ“-ideals in TÎ“-semirings.Â